Sociocultural origins of Turkish educational reforms and ideological origins of late Ottoman intellectuals (1908-1930) - Gunduz, Mustafa (Routledge Journals, Taylor & Francis Ltd, 2009)
The modern Turkish state and society have been greatly influenced by reforms of the education system. Second Constitutional Period reforms can be viewed as the preparatory stage of Republican reforms and a time when many of the later reforms were planned and given limited application. In this way both periods contributed to the foundation of modern Turkey. The innovations pioneered by Late Ottoman intellectuals stemmed from various origins, mostly European positivists and materialist philosophers. American pragmatism was added as an ideological source during the foundation of the Republic. It can be observed that ideological trends took root from Ottoman times according to the degree that intellectuals were affected by them. In this paper, the ideological origins of educational reforms during the Second Constitution Period have been studied in relation to the influence of European philosophers on Ottoman intellectuals of the time and their ideological environments. Late Ottoman intellectuals were found to have been largely affected by France's positivism, German's materialism and Comte, Durkheim, Buchner and Spencer. The paper reveals how modern Turkey's educational philosophy parameters have been shaped by these intellectuals' ideas.
Keywords: Turkish Republic educational reforms; educational philosophy; educational sociology; late Ottoman intellectuals; second constitution period; positivism; materialism